A sterile self-assembled sericin hydrogel via a simple two-step process. (December 2019) - Zhang, Yeshun; Zhao, Yuying; He, Xiaobai; Fang, Ai; Jiang, Rulan; Wu, Tangfeng; Chen, Heguang; Cao, Xitao; Liang, Peisheng; Xia, Dingguo; Zhang, Guozheng
Abstract: In materials science and engineering, designed and well-ordered self-assembled hydrogel with excellent biocompatibility and nontoxic properties is an inviting issue. In this study, a novel self-assembled sericin hydrogel was prepared by a simple-two-step process containing milling and high temperature and high pressure. It is worthwhile pointing out that the sericin with high extraction rate (95%) for fabricating sericin hydrogel was isolated from fibroin-deficient mutant silk cocoons. The hydrogel was formed under a mild condition without introducing any other toxic or harmful substances and its gelling time could be controlled by sericin concentration, temperature or pH values. Moreover, as long as the sericin solution is kept in a bioclean circumstance, the sterile sericin hydrogel can be achieved and no need to sterilize. Furthermore, this hydrogel possesses high porosity, degradation. In addition, the hydrogel system is suitable as a carrier of cells or bioactive molecules contribute from its excellent cell-adhesive capability, effectively promoting cell attachment, proliferation, and a sustained manner for drug release. In summary, our study indicates that the self-assembly sericin hydrogel could be promising candidates in soft tissue engineering applications. Graphical abstract: Image 1 Highlights: We first report a sterile self-assembled sericin hydrogel via a simple two-step process without introducing any other toxic or harmful substances. The sericin hydrogel that is formed by the sericin with high extraction rate (95%) under mild and bioclean conditions does not need further sterilization. Gelation times of the hydrogel could be controlled from minutes to hours by regulated sericin concentration, temperature and pH. This hydrogel possesses degradation, degradation products with near-neutral pH, high porosity, high compressive modulus. The hydrogel system is compatible for hosting cell and bioactive molecules owing to its excellent cell-adhesive capability, effectively promoting cell attachment, proliferation and delivering bioactive reagent in a sustained manner.